Durability of Thermally Modified Western Hemlock Lumber Against Wood Decay Fungi - Presley, Gerald; Cappellazzi, Jed; Eastin, Ivan (Frontiers in Forests and Global Change, 2022)
The chemical modification of wood is gaining popularity as a treatment to increase wood durability, particularly in jurisdictions where restrictions on the use of chemical impregnation are increasing. This work measures the impact of thermal modification of western hemlock lumber durability against decay fungi. Western hemlock lumber was thermally modified using a cycle with temperatures ranging from 80-170ºC and was cut into standard 19 mm blocks for testing according to AWPA method E10. Performance of thermally modified wood was measured against two brown rot fungi, Rhodonia placenta and Gloeophyllum trabeum and one white rot fungus, Trametes versicolor over an 8, 12 and 16-week incubation period. Unmodified western hemlock wood, untreated southern pine and copper azole-treated southern pine were included for comparison. Thermal modification resulted in a slight improvement in durability against Gloeophyllum trabeum, but not Rhodonia placenta compared to untreated western hemlock which caused 50.3% and 52.2% mass loss in thermally modified western hemlock after 16 weeks, respectively. T. versicolor caused a 21.2% mass loss after 16 weeks, but this value was not statistically different than untreated western hemlock (p=0.46). For comparison, copper azole-treated southern pine showed only an average of 0% and 15% mass loss when exposed to G. trabeum or R. placenta for 16 weeks, respectively. Together, these data indicate that while there may be some protective effect of thermally modifying western hemlock, further development of treatment processes are needed to improve the durability of thermally modified western hemlock.